EVALUATION OF THE UTILIZATION OF A RICE PROCESSING TECHNOLOGY AMONG WOMEN FARMERS IN THE CENTRAL ZONE, NIGERIA - Ike Nwachukwu; A. A. Jibowo (Journal of Agricultural Extension, 2018)
The National Cereals Research Institute developed and disseminated a rice processing technology more than a decade ago. To evaluate the utilization of the technology in the Central Zone, 223 rice processing women were randomly selected from four states for data collection, using an interview schedule. The results show that the level of utilization is low. Majority of the respondents are not aware of the technology. For those who are aware, only three out of the six practices are effectively utilized.